2010
DOI: 10.1002/j.0022-0337.2010.74.9.tb04950.x
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices for Dental Sealants in Community Service‐Learning

Abstract: Community service-learning (CSL) in predoctoral dental education might be an effective tool for increasing sealant use by dentists-thus benefitting underserved children while facilitating students' learning of a clinical procedure in a real-life setting. This study reviewed the scientific literature on this topic in order to 1) evaluate the reasons for low sealant use among dentists, 2) consider important aspects of sealant use in community settings, and 3) identify best practices to use as guidelines for CSL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…The 18 studies addressing dental ethics and social responsibility encompassed topics such as ethics pedagogy, ethical commitment, professionalism, ethical reasoning, and curricular incorporation of these topics. We identified that ethics education was associated with professionalism and social responsibility in these studies . One of these studies supported the continuous instruction of ethics throughout the dental program to better produce clinicians who can identify and understand the needs of their community .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The 18 studies addressing dental ethics and social responsibility encompassed topics such as ethics pedagogy, ethical commitment, professionalism, ethical reasoning, and curricular incorporation of these topics. We identified that ethics education was associated with professionalism and social responsibility in these studies . One of these studies supported the continuous instruction of ethics throughout the dental program to better produce clinicians who can identify and understand the needs of their community .…”
Section: Resultsmentioning
confidence: 98%
“…A large number of studies discussed introspection and self‐reflection. These are fostered through reflective writing and learning exercises, as well as through the use of critical incident reports that promote students’ self‐evaluation of their experiences and potential biases …”
Section: Resultsmentioning
confidence: 99%
“…This would ensure maximum sealant performance “credit” would be given to the provider. Accounting for a deferment period between a PDV and sealant placement was necessary, due to the potential clinical, behavioral, or scheduling reasons for delaying sealant applications during a PDV 18,19 . In cases where children saw more than one dentist for a PDV, their eligible teeth were counted under each dentist seen in the study period.…”
Section: Methodsmentioning
confidence: 99%
“…Accounting for a deferment period between a PDV and sealant placement was necessary, due to the potential clinical, behavioral, or scheduling reasons for delaying sealant applications during a PDV. 18,19 In cases where children saw more than one dentist for a PDV, their eligible teeth were counted under each dentist seen in the study period. In the event a child had more than one PDV to the same dentist in the same year, his or her eligible teeth were counted on the last PDV of the fiscal year.…”
Section: Operationalizing the Nppmmentioning
confidence: 99%
“…One potential strategy to increase the coverage of school-based programs is the integration of the application of fissure sealant into the curriculum of dental students through the community-based learning (CBL) modules. Such CBL modules provide opportunities for students to be socially responsible, culturally competent and aware of the determinants of health in underserved communities (Aleksejūnienė et al, 2010).…”
mentioning
confidence: 99%